Engaging the next generation of healthcare professionals in genomics: planning for the future. (January 2014) - Callier, Shawneequa L; Toma, Ian; McCaffrey, Timothy; Harralson , Arthur F; O'Brien, Travis J
There is broad agreement that healthcare professionals require fundamental training in genomics to keep pace with scientific advancement. Strong models that promote effective genomic education, however, are lacking. Furthermore, curricula at many institutions are now straining to adapt to the integration of additional material on next-generation sequencing and the bioethical and legal issues that will accompany clinical genomic testing. This article advocates for core competencies focused on job function, which will best prepare providers to be end-users of healthcare information. In addition, it argues in favor of online and blended learning models that incorporate student genotyping and specific training in the ethical, legal and social issues raised by genomic testing.